PERAN SISTEM PENDIDIKAN MUHAMMADIYAH DALAM PENCETAKAN KADER DAN TRANSFORMASI SOSIAL: SEBUAH STUDI LITERATUR SISTEMATIS - Habibullah; Faruq Fadhlillah, Fatin; Adam Rasuli, Moh.; Khairul Anam, Rifqi (As-Sulthan Journal of Education, 2026)
The Muhammadiyah education system has long been considered a key instrument not only in knowledge transfer but also in the reproduction of Islamic social movements in Indonesia. This study aims to synthesize the findings of scientific literature regarding the dual role of the system: as an engine for cadre formation and as an agent for social transformation. The method used is a Systematic Literature Review with a qualitative approach to journal articles, theses, and dissertations published between 2014-2024, sourced from Google Scholar and Garuda Portal databases. The synthesis results indicate that: (1) Cadre formation is built through a coherent trilogy of mechanisms ideological curriculum (Al-Islam and Kemuhammadiyahan), activism in autonomous organizations (IPM/IMM), and environmental role modeling; (2) Social transformation manifests in a graded spectrum, from charitable services and economic empowerment to policy advocacy, executed by educational outputs through Muhammadiyah's philanthropic network; (3) These two functions form a self-sustaining dialectical cycle, where education produces cadres, cadres become agents of change, and the success of that change reproduces legitimacy and new resources to attract the next generation of cadres. This study concludes that the sustainability of the Muhammadiyah movement stems from the capacity of its education system to function as a self-reproducing ecosystem. These findings provide a theoretical contribution in the form of an analytical model for the sustainability of education-based social movements and practical implications for strengthening the institutional capacity of community organizations.